Path Analysis of the Decomposition Method to Know the Factors Influence on the Completion of the Thesis - Primajati, Gilang (Balai Publikasi Indonesia, 2023)
This study aims to perform modeling and determine the factors that significantly and not significantly influence the completion of the thesis. The analysis used is the path analysis of the decomposition method. The data used is primary data by distributing questionnaires. Based on the results of the analysis that has been done, the path analysis model for the factors that influence the completion of the thesis are: The factors that significantly effect are facilities (), selection of specialization courses (), and selection of courses (). While lecturer factor () and motivation factor () have no effect. Supporting facilities factor and selection of supporting courses factor only directly affect the completion of minithesis. While the selection of specialization courses also has indirect effect to the completionof the thesis.